STAGES OF THE CURRENT STATE OF LAND FORESTRY PURPOSES AND FEATURES OF THEIR USE IN THE CONTEXT OF THE LEGAL REGIME - Bondar Volodymyr Nalkovych (World Science, 2020)
The article analyzes the structure of the land fund, the distribution of Ukraine’s forest area by predominant tree species, and states that the division of land by categories is a dynamic process, whenever in the course of economic activity on land there may be a need to change its purpose. Determining and changing the ownership of a land plot to a certain category of land is the prerogative of public authorities - state and local self-government, which are endowed with such powers. The analysis of forest cover in Ukraine in terms of natural zones and structure of land for forestry purposes in Ukraine, where from the total area of forestry lands and forests on other categories of lands is 10.8 million hectares, of which 9.7 million hectares are covered with forest vegetation. The analysis of the given data testifies to an uneven arrangement of the specified category of lands of the territory of Ukraine. In particular, they are concentrated mainly in Polissya and the Ukrainian Carpathians. The stages of legal regulation and use of forest lands are proposed. Regarding the solution of these two problems lies in the plane of decision-making on land use, establishing a socially optimal purpose of land, compliance with land legislation, promoting reforestation and afforestation; stimulating the preservation and increase of forest land productivity, which requires the use of levers of influence on land and forest users; irrational use of forest lands, which leads to loss of potential benefits of the landowner.